10.1016/s1544-8800(05)70332-8 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Child life specialists (CLSs) are increasingly recognized in paediatric practice, yet evidence regarding the efficacy of CLS intervention in children remains insufficient. This review aims to comprehensively evaluate the intervention effects of CLSs on paediatric patients. METHODS: Six databases (PubMed, Web of Science, Embase, Cochrane Library, CINAHL and APA PsycArticles) were systematically searched using subject terms and free terms. Randomized controlled trials (RCTs) assessing CLS effects on paediatric pain and psychological outcomes were included, with searches from database inception through 30 January 2026. Two reviewers independently screened literature and extracted data. Methodological quality was assessed using the Cochrane Risk of Bias tool. Meta-analysis was conducted using Stata/MP 18.0, calculating standardized mean difference (SMD) with 95% confidence interval (CI) via a random-effects model. RESULTS: The initial search yielded 1140 records, and 12 studies (n = 1096 participants) were ultimately included in the analysis. The included studies primarily originated from the United States and Canada. Intervention settings included inpatient units, outpatient clinics and emergency departments. The meta-analysis revealed that, compared to conditions without CLS involvement, the presence of CLSs may alleviate children's pain (SMD = -0.28, 95% CI -0.49 to -0.07, p = 0.009), distress (SMD = -0.26, 95% CI -0.48 to -0.05, p = 0.018) and anxiety (SMD = -0.37, 95% CI -0.65 to -0.01, p = 0.007) during medical procedures and treatments. However, the effect on alleviating children's fear was not statistically significant (SMD = -0.11, 95% CI -0.32 to 0.10, p = 0.290). CONCLUSION: Current evidence supports the potential of CLSs to alleviate paediatric pain, psychological distress and anxiety. However, their efficacy in reducing fear requires further validation. Despite the uncertainties involved, the potential value of CLSs in clinical practice warrants broader recognition.